2001
DOI: 10.1034/j.1600-0854.2001.002006414.x
|View full text |Cite
|
Sign up to set email alerts
|

The Actin Cytoskeleton is Required for the Trafficking of the B Cell Antigen Receptor to the Late Endosomes

Abstract: The B cell antigen receptor (BCR) plays two central roles in B cell activation: to internalize antigens for processing and presentation, and to initiate signal transduction cascades that both promote B cells to enter the cell cycle and facilitate antigen processing by accelerating antigen transport. An early event in B cell activation is the association of BCR with the actin cytoskeleton, and an increase in cellular F-actin. Current evidence indicates that the organization of actin filaments changes in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
87
1

Year Published

2001
2001
2008
2008

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 59 publications
14
87
1
Order By: Relevance
“…In this study, we found that the increase in BCR residency in the surface-signaling microdomains and BCR-triggered protein phosphorylation was associated with a decrease in BCR internalization. This is consistent with our previous observation that an inhibition of BCR internalization slowed down the attenuation of BCR-triggered protein tyrosine phosphorylation (34). These results suggest that inhibition of internalization is one of the mechanisms for stabilizing surface-signaling microdomains.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In this study, we found that the increase in BCR residency in the surface-signaling microdomains and BCR-triggered protein phosphorylation was associated with a decrease in BCR internalization. This is consistent with our previous observation that an inhibition of BCR internalization slowed down the attenuation of BCR-triggered protein tyrosine phosphorylation (34). These results suggest that inhibition of internalization is one of the mechanisms for stabilizing surface-signaling microdomains.…”
Section: Discussionsupporting
confidence: 82%
“…The surface BCR of CH27 and splenic B cells was labeled with Cy3-conjugated Fab of goat anti-mouse IgM Ab (Cy3-Fab anti-IgM) at 4°C in the presence or absence of either 20 g/ml B-anti-Ig or 20 g/ml B-anti-Ig plus 20 g/ml avidin. As previously shown, B-anti-Ig does not compete with Fab-anti-IgM to bind to the BCR (5,34). After incubation at 37°C for 60 min, cells were cooled to 4°C and incubated with FITC-CTX without permeabilization to label the surface G M1 .…”
Section: Ag Valency and The Formation Of Bcr-signaling Microdomainsmentioning
confidence: 99%
“…BCR activation induces reorganization of the actin cytoskeleton (24,25). The presence of two ABDs in Abp1 implies that its cellular redistribution may rely on BCR-induced actin cytoskeleton reorganization.…”
Section: Bcr-induced Abp1 Redistribution Depends On the Actin Cytoskementioning
confidence: 99%
“…We previously demonstrated that the dynamic property of the actin cytoskeleton was required for signal-stimulated BCR internalization. BCR endocytosis is blocked at the pinching-off step during clathrin-coated vesicle formation in the absence of the functional actin cytoskeleton (24). Stoddart et al (26) suggested an actin cytoskeleton-dependent and clathrin-independent BCR internalization pathway in DT40 chicken B cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation